Homelessness and Insect-Borne Illness Risks: A Study of the Unsheltered Homeless Population in Cambridge, Massachusetts - Hooper, Michael (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
This paper asks how people experiencing homelessness and who are unsheltered manage the risks posed by insect-borne illnesses. Concerns over such risks have increased with recognition that climate change is expanding the range of many insect vectors for serious illnesses. In response to this threat, many cities – including Cambridge, Massachusetts (MA), where this study was conducted – have started to take efforts to protect the public. Nonetheless, these have often paid limited attention to the unsheltered. Drawing on interviews with 85 unsheltered residents this paper examines how these individuals understand and respond to insect-borne illness risks. The results show interviewees hold diverse views, with many having some awareness of such risks and taking a variety of steps to manage their exposure. In the absence of regular access to insect repellent many interviewees opt for a variety of alternative approaches, likely varying in effectiveness, to prevent and respond to insect bites. Some interviewees, however, are either unaware of their risks or unable to take steps to protect themselves. The results provide insights for city officials, advocates for the unsheltered, and planners as they try to protect highly vulnerable groups in the face of increasing climate-driven risk from insect-borne illnesses.